THE EFFECT OF SERVICE QUALITY ON MEMBER SATISFACTION MEDIATED BY COOPERATIVE IMAGE - Nursiva, Rizka Tiara (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
The objective of this research is to prove empirically the effect of mediation of cooperative image on the correlation between service quality and member satisfaction of KBA Fiskal. The sample sized used is 120 people refers to the theory of Roscoe (1975) with simple random sampling technique. Data was collected using questionnaires and analyzed by using SPSS Statistics. The result of this research concludes that service quality has positive and significant effects on member satisfaction, service quality has positive and significant effects on cooperative image, cooperative image has positive and significant effects on member satisfaction and the cooperative image partially mediates the correlation between service quality and member satisfaction at KBA Fiskal.